2011
DOI: 10.1057/jors.2010.32
|View full text |Cite
|
Sign up to set email alerts
|

An aggregate–disaggregate intermittent demand approach (ADIDA) to forecasting: an empirical proposition and analysis

Abstract: Intermittent demand patterns are characterised by infrequent demand arrivals coupled with variable demand sizes. Such patterns prevail in many industrial applications, including IT, automotive, aerospace and military. An intuitively appealing strategy to deal with such patterns from a forecasting perspective is to aggregate demand in lower-frequency 'time buckets' thereby reducing the presence of zero observations. However, such aggregation may result in losing useful information, as the frequency of observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 23 publications
3
108
0
1
Order By: Relevance
“…Rostami-Tabar et al (2013) look into identifying an optimal aggregation level when the disaggregate process is either MA(1) or AR(1) and find that in general the higher the aggregation the lower the forecast errors are, when forecasting by single exponential smoothing. For more complex processes Nikolopoulos et al (2011) demonstrate that forecasting accuracy does not change monotonically as the aggregation level increases.…”
Section: Introductionmentioning
confidence: 91%
“…Rostami-Tabar et al (2013) look into identifying an optimal aggregation level when the disaggregate process is either MA(1) or AR(1) and find that in general the higher the aggregation the lower the forecast errors are, when forecasting by single exponential smoothing. For more complex processes Nikolopoulos et al (2011) demonstrate that forecasting accuracy does not change monotonically as the aggregation level increases.…”
Section: Introductionmentioning
confidence: 91%
“…Temporal aggregation is known to be applied widely in practical military settings (very sparse data), the after-sales industry (service parts) and elsewhere. Nikolopoulos et al (2011) demonstrated the value of (non-overlapping) temporal aggregation in such a context. Although the paper under concern was exploratory in nature, it provided some much-needed empirical evidence of the potential benefits of using temporal aggregation in a supply chain context by means of experimenting with the demand histories of 5,000 stock keeping units from the Royal Air Force (UK).…”
Section: Temporal Aggregationmentioning
confidence: 95%
“…Building on those empirical results, some theoretical analysis was presented for data following an AR(1) and MA(1) process by Rostami-Tabar et al (2013) and a more general ARMA(1,1) process by Rostami-Tabar et al (2014). This analysis led to theoretically determined optimum aggregation levels for the ADIDA framework (as opposed to the empirically determined optimum levels of aggregation suggested by Nikolopoulos et al, 2011) under specific demand generation processes). Further theoretical developments for both fast and slow moving data were presented by Spithourakis et al (2014) providing theoretical bounds for the temporal aggregation process to be leading to improvements in forecasting accuracy.…”
Section: Temporal Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conocido como método ADIDA (Aggregate, Disaggregate, Intermittent Demand Approch, por sus iniciales en inglés) transforma la serie inicial en otra serie modificando la frecuencia en que se agregan las demandas de esos periodos, por ejemplo, de mensual a trimestral. Con la serie alternativa se realiza la extrapolación y luego se procede con la desagregación para estimar la previsión de la demanda para un determinado período [15].…”
Section: Métodos Clásicos De Previsiónunclassified